Respons Perkecambahan Benih Kopi Liberika (Coffea liberica W. Bull Ex Hiern) Tungkal Jambi Terhadap Konsentrasi Ekoenzim dan Lama Perendaman: The Response of Liberica Coffee Seed Germination (Coffea liberica W. Bull Ex Hiern) from Tungkal Jambi to Eenzyme Concentration and Soaking Duration - Devi Triana; Gusniwati, Gusniwati; Indraswari, Elly; Kartika, Elis; Neliyati, Neliyati (Jurnal Silva Tropika, 2025)
ABSTRACT Liberica coffee from Tungkal Jambi is an important plantation commodity in Jambi Province; however, seedling development is constrained by slow seed germination due to physical dormancy, resulting in low nursery efficiency. Seed soaking using eco-enzyme has the potential to serve as an alternative approach to overcome this constraint. This study aimed to evaluate the germination response of Liberica coffee seeds to different eco-enzyme concentrations and soaking durations. The experiment was conducted at the Teaching and Research Farm Greenhouse, Faculty of Agriculture, Universitas Jambi, from January to April 2025, using a completely randomized factorial design with two factors: eco-enzyme concentration (0, 25, 50, 75, and 100%) and soaking duration (12 and 24 h). The observed variables included germination percentage, longest hypocotyl length, longest root length, hypothetical vigor index, and seedling dry weight. The results showed no interaction between eco-enzyme concentration and soaking duration. Application of eco-enzyme at concentrations of 25–100% increased the longest root length of Liberica coffee seedlings, but did not improve other germination and seed vigor parameters. The best germination response of liberica coffea seeds is obtained at an ecoenzyme concentration of 25% and a soaking time of 12 hours.   Keywords:  ecoenzyme, germination, liberica tungkal jambi coffea   ABSTRAK Kopi Liberika Tungkal Jambi merupakan komoditas perkebunan penting di Provinsi Jambi, namun pengembangan bibitnya masih terkendala oleh lambatnya perkecambahan benih akibat dormansi fisik, sehingga menurunkan efisiensi pembibitan. Perlakuan perendaman benih menggunakan ekoenzim berpotensi menjadi salah satu solusi untuk mengatasi kendala tersebut. Penelitian ini bertujuan mengevaluasi respons perkecambahan benih kopi Liberika terhadap variasi konsentrasi ekoenzim dan lama perendaman. Penelitian dilaksanakan di Rumah Kaca Teaching and Research Farm Fakultas Pertanian Universitas Jambi pada Januari–April 2025 menggunakan Rancangan Acak Lengkap (RAL) faktorial dua faktor, yaitu konsentrasi ekoenzim (0, 25, 50, 75, dan 100%) dan lama perendaman (12 dan 24 jam). Variabel yang diamati meliputi daya berkecambah, panjang hipokotil terpanjang, panjang akar terpanjang, indeks vigor hipotetik, dan bobot kering kecambah. Hasil penelitian menunjukkan tidak terdapat interaksi antara konsentrasi ekoenzim dan lama perendaman. Pemberian ekoenzim pada konsentrasi 25–100% mampu meningkatkan panjang akar terpanjang kecambah kopi Liberika, namun belum meningkatkan variabel perkecambahan dan vigor benih lainnya. Respons perkecambahan benih kopi liberika terbaik diperoleh pada konsentrasi ekoenzim 25% dan lama perendaman 12 jam.   Kata kunci: ekoenzim, kopi liberika tungkal jambi, perkecambahan